Kompensasi dan Motivasi Terhadap Kinerja Karyawan - Sri Sahbany; Detty Agustin Riscal; Junaidin Junaidin (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to determine the influence of compensation and work motivation on employee performance at PT. Aditya Farmatama Mataram Branch. The research was carried out using a survey method through a purposive sampling approach with the consideration that the respondents were all employees of PT. Aditya Farmatama Mataram Branch as many as 30 people. Data collection was carried out using a questionnaire that was distributed directly to respondents. Data analysis was carried out using descriptive analysis and multiple lienar regression analysis. The results of the analysis showed that compensation and work motivation together had a significant effect on employee performance, compensation and work motivation partially had a significant effect on employee performance, and work motivation had a more dominant effect than compensation on employee performance.